Vrednotenje prisotnosti damjaka (Dama dama) na ugrezninskem območju velenjskega premogovnika - Pokorny, Boštjan (Zbornik gozdarstva in lesarstva, 1999)
A relative viable population of fallow deer (Dama dama) lives in the area around the planned kale Landscape Park, thus the influence of the introduced species over the conservation goals is evaluated in the article. An impact on the phytocenosis (study of favourite plant taxa in the species nutrition) and zoocenosis (field observations of interspecific relationships, fallow deer influence over the roe deer vitality, a risk assessment for the higher levels of the food web due to heavy metal accumulation) as well as an educational anda recreational value of the species (inquiry of visitors in the nearby recreational area) were studied. The influence over the aggregate of goals, quantified by the assessment of the influence on one particular goal and considering the relative importance of that goal, is slightly positive (+0.417). Accordingly, the presence of fallow deer in the area of interest is acceptable. However, the preservation of habitat heterogeneity and the conservation of landscape structure in the entire Velenje coal-mine subsidencearea are perquisites for the fallow deer's existence as well as for the conservation of biodiversity in the alek Valley.
Keywords: damjaki; habitat; ogroženost; Šalek Valley; Šaleška dolina; zoogeografija